PENGARUH PERSEPSI RISIKO DAN KEPERCAYAAN LEMBAGA TERHADAP KEPUTUSAN INVESTASI EMAS DENGAN LITERASI KEUANGAN SYARIAH SEBAGAI VARIABEL MODERASI - Herawati Khotmi; Dewi Rispawati (PEKA, 2026)
In the age of global economic uncertainty, gold is a well-founded safe investment choice. This study is conducted to analyze how risk perception and belief affect gold investment decisions with a moderating variable which is financial literacy in Islamic finance. The research method adopted a quantitative approach with purposive sampling and concentrated on Muslim investors that have either invested in physical or digital gold to achieve the research goal in Lombok, with 100 respondents. Data analysis was conducted based on SEM-PLS using Structural Equation Modelling. Trust in institutions has been found not significantly related to investing in gold, while financial literacy and risk perception were found to be the two key factors influencing investment in gold based on the study findings. In addition, financial literacy in Islamic banking acts as a moderating variable, strengthening the relationship between institutional trust and risk perception in investment decisions. These results reinforce that financial literacy in Islamic principles is not only basic knowledge but should be a key contributor to the quality of the decision-making process in the investment realm by Islamic principles and is necessary for improvement of investment quality in line with Islamic principles. Therefore, this analysis also shows that there is likely to become more emphasis on financial literacy among investment professionals (through social and educational channels) so that investors can make more thoughtful decisions in making more rational investments and have more confidence in the integrity of investing institutions. This study therefore serves to advance the theoretical literature for behavioural finance and Islamic economics and offers practical suggestions for a gold investment ecosystem grounded on Islamic finance principles.